Prendre le risque d’être affectée - Laura Ferilli (Sociologies, 2014)
The methods which are traditionally applied in social sciences often induce a dichotomy between scholars and those being studied, thus suggesting the existence of differing humanities. Indeed the usual empiricist stance often generates static study conditions where it is implied that the subjects do not function in the same way as the scientists in many aspects. An example of this would be the way in which each person tries their best to control their image through showcase speech. However, whatever the situation, nothing is straightforward; neither behaviour, nor words. Certain things must be experienced and lived from a specific point of view so as to be grasped in all their sensitive dimensions, or in their intensity, in Jeanne Faveret-Saada’s terms. The risk of involvement must be taken so as to be protected from the temptation of dichotomies.